The way of the Prophets - Philips, Abu Ameenah Bilal; One Islam Publications (N.S.W, Australia : One Islam Publications, 2006)
All the prophets, from the first to the last brought the same message, to worship Allah alone, without any partners. In our time the message still remains, in the form of the Holy Quran, and the guidance of the final prophets, Muhammad, peace and blessing be upon him. This talk demonstrates how the only way to salvation is to follow these two sources of guidance
Title from title screen
Presenter : Abu Ameenah Bilal Philips
Keywords: Prophets; Islam